Design of an X-ray plane prototype with Android-based absorption dose estimation calculation - Ari Firmansyah; Afdhal Muttaqin (Universitas Sebelas Maret, 2025)
The development of an android-based radiation dose estimation system for X-ray plane, which incorporates tube voltage and tube current settings, is anticipated to reduce costs and minimize radiation doses. This prototype employs an X-ray tube with a single tank low-frequency specification and a tube current capability at high tension transform (HTT) of 10 mA, an exposition time of 0.1 s, and variations in tube voltage generated by 45 kV, 50 kV, and 60 kV. The prototyping phase encompasses the design of the hardware components, including the x-ray tube generator, voltage divider circuit, power supply, and Arduino Nano, which serves as the data processing unit. The software design employs the Skript programming language for deployment on Android and ESP32 devices. This involves the initial installation of the Blink application on Android via the Play Store. The prototype underwent a series of tests, including hardware testing, reproducibility testing, and peak voltage testing. Irradiation time testing and dose in microGray with the amount of CV passing at 0.05 (0.016) were also conducted. Additionally, software testing was performed to assess the accuracy, reproducibility, linearity, and dose estimation capabilities of the tube voltage settings.